2003
DOI: 10.1093/emboj/cdg213
|View full text |Cite
|
Sign up to set email alerts
|

Domain organization and structure-function relationship of the HET-s prion protein of Podospora anserina

Abstract: The [Het-s] infectious element of the fungus Podospora anserina is a prion protein involved in a genetically controlled cell death reaction termed heterokaryon incompatibility. Previous analyses indicate that [Het-s] propagates as a self-perpetuating amyloid aggregate. The HET-s protein is 289 amino acids in length. Herein, we identify the region of the HET-s protein that is responsible for amyloid formation and prion propagation. The region of HET-s spanning residues 218-289 forms amyloid fibers in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
260
0
18

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(284 citation statements)
references
References 35 publications
(52 reference statements)
6
260
0
18
Order By: Relevance
“…This observation does not dismiss the fact that IBs might indeed have an amyloid structure, because even amyloids do not incorporate their entire polypeptide length into the highly packed b-sheet structure as seen in yeast prions (Morgan et al, 2008). The secondary structure content analysis of IBs confirmed that there are fibrillar and nonfibrillar regions included (Balguerie et al, 2003). Moreover comparison of IB formation with an amyloid b-formation revealed a common formation mechanism: primary establishment of an inter-backbone, hydrogen-bonded network that stabilizes b-sheet-rich fibrillar structures and drives the aggregation force.…”
Section: Protein Homeostasis and Bacterial Cellular Responses To Aggrmentioning
confidence: 97%
“…This observation does not dismiss the fact that IBs might indeed have an amyloid structure, because even amyloids do not incorporate their entire polypeptide length into the highly packed b-sheet structure as seen in yeast prions (Morgan et al, 2008). The secondary structure content analysis of IBs confirmed that there are fibrillar and nonfibrillar regions included (Balguerie et al, 2003). Moreover comparison of IB formation with an amyloid b-formation revealed a common formation mechanism: primary establishment of an inter-backbone, hydrogen-bonded network that stabilizes b-sheet-rich fibrillar structures and drives the aggregation force.…”
Section: Protein Homeostasis and Bacterial Cellular Responses To Aggrmentioning
confidence: 97%
“…1). The Het-s protein lacks the Asn/Gln-rich region characteristic of the yeast prions identified so far, although it is similarly divided into a globular functional region and a flexible prion domain [22]. The relationship between domain structure and function for the PrP protein is more complex.…”
Section: Overviewmentioning
confidence: 99%
“…The Ure2 system is therefore a useful model not only to investigate the prion concept, but also to understand the properties of Gln/ Asn-repeat proteins and hence the molecular basis of the related diseases. [27,29,58], Sup35 [114,115], Rnq1 [13], Het-s [22] and PrP [23,24,116,117]. The functional regions are as indicated.…”
Section: Introductionmentioning
confidence: 99%
“…The missing resonances of the remaining residues are probably a consequence of dynamical or structural heterogeneity 19 . Deviations of the combined 13 Cα/ 13 Cβ chemical shifts from random coil values were used to identify the type of secondary structure present in HET-s(218-289) fibrils. Negative deviations (Fig.…”
mentioning
confidence: 99%